Pan-Cancer Transcriptomic Analysis Identifies PLK1 Crucial for the Tumorigenesis of Clear Cell Renal Cell Carcinoma - Qian Y; Li Y; Chen K; Liu N; Hong X; Wu D; Xu Z; Zhou L; Xu L; Jia R; Ge YZ (Dove Medical Press, 2022)
Yiguan Qian,* Yang Li,* Ke Chen,* Ning Liu, Xi Hong, Di Wu, Zheng Xu, Liuhua Zhou, Luwei Xu, Ruipeng Jia, Yu-Zheng Ge Department of Urology, Nanjing First Hospital, Nanjing Medical University, Nanjing, Jiangsu, People's Republic of China*These authors contributed equally to this workCorrespondence: Ruipeng Jia; Yu-Zheng Ge, Department of Urology, Nanjing First Hospital, Nanjing Medical University Nanjing, Jiangsu, People's Republic of China, Tel +86-15850675660, Email ruipengj@163.com; geyuzheng@njmu.edu.cnBackground: Polo-like kinase 1 (PLK1) belongs to polo-like kinases family and affects cell cycles. However, the role of PLK1 in some malignant tumors remains unclear.Methods: To obtain a comprehensive view of PLK1 expression patterns, public databases including The Cancer Genome Atlas, Cancer Cell Line Encyclopedia, the Genotype-Tissue Expression, and human cell landscape databases were employed. The correlation of PLK1 expression with prognosis, immune infiltrations, immune checkpoint genes, tumor mutational burden (TMB), microsatellite instability (MSI), mismatch repair (MMR), and DNA methylation was examined. Besides, we validated the results of clear cell renal cell carcinoma (ccRCC) in two cohorts, with quantitative real-time PCR, Western blot, and loss-of-function experiments.Results: By mining public datasets, we discovered that PLK1 expression in tumor tissues and cancer cell lines displayed heterogeneity compared to normal controls across different cancers. Besides, high expression of PLK1 results in shorter survival time in 15 cancer types, especially in ccRCC. PLK1 expression showed strong association with immune cell infiltration and immune checkpoint genes across cancer types. Moreover, we identified a strong association between PLK1 expression and TMB, MSI MMR, and DNA methylation. PLK1 was validated to be highly expressed in ccRCC tissues and promote ccRCC cell proliferation, migration, invasion, and cell cycle. Mechanistically, PLK1 could regulate forkhead box protein M1 and target cell cycle-associated genes to participate in cell cycle control.Conclusion: PLK1 has important prognostic value and is associated with tumor immunity across cancer types including ccRCC.Keywords: PLK1, pan-cancer analysis, ccRCC, biomarker, tumor immunity